Gingival depigmentation and pink aesthetics: a case report - Kafle, Shristi (Journal of Chitwan Medical College, 2020)
The colour of gingiva has a tremendous impact on the overall aesthetics of an individual. Clinically, gingival melanin hyperpigmentation is presented as ‘black gum’,which is a common aesthetic problem especially for those who have a gummy smile. It mainly affects the self-esteem, appearance, and confidence of an individual, and it can also have a psychological impact on many patients. Gingival depigmentation can be carried out as part of its treatment using various methods. A case is reported here where scalpel surgery was performed.